(untitled) (Scientific journal of the Fergana State University, 2023)
The dependence of the viscosity of starch sizing compound gels on the content of various modifiers in them at different temperatures is studied. The influence of the PVA concentration in the sizing composition on the main parameters of the finished yarn was determined. The main performance indicators of the developed sizing compounds in sizing the cotton yarn are studied